Lack of association between alopecia areata and HLA class I and II in a southeastern Brazilian population - Ângela Marques Barbosa; Luiz Euribel Prestes-Carneiro; Aldri Roberta Sodoschi Sobral; Marcelo Jun Sakiyama; Bruna Cerávolo Lemos; Marilda Aparecida Milanez Morgado de Abreu; Luciana Leite Crivelin Martos; Ricardo Alberto Moliterno (Sociedade Brasileira de Dermatologia, 2016)
Abstract: Background: Alopecia areata (AA) is a common disorder of unknown etiology that affects approximately 0.7% to 3.8% of patients among the general population. Currently, genetic and autoimmune factors are emphasized as etiopathogenic. Studies linking Human Leukocyte Antigens (HLA) to AA have suggested that immunogenetic factors may play a role in the disease's onset/development. Objectives: To investigate an association between AA and HLA class I/II in white Brazilians. Methods: Patients and control groups comprised 33 and 112 individuals, respectively. DNA extraction was performed by column method with BioPur kit. Allele's classification was undertaken using the PCR-SSO technique. HLA frequencies were obtained through direct counting and subjected to comparison by means of the chi-square test. Results: Most patients were aged over 16, with no familial history, and developed partial AA, with no recurrent episodes. Patients showed a higher frequency of HLA-B*40, HLA-B*45, HLA-B*53 and HLA-C*04 compared with controls, although P was not significant after Bonferroni correction. Regarding HLA class II, only HLA-DRB1*07 revealed statistical significance; nevertheless, it featured more prominently in controls than patients (P=0.04; Pc=0.52; OR=0.29; 95%; CI=0.07 to 1.25). P was not significant after Bonferroni correction. Conclusions: The development of AA does not seem to be associated with HLA in white Brazilians, nor with susceptibility or resistance. The studies were carried out in populations with little or no miscegenation, unlike the Brazilian population in general, which could explain the inconsistency found.